2013
DOI: 10.1186/1752-4458-7-5
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives and concerns of clients at primary health care facilities involved in evaluation of a national mental health training programme for primary care in Kenya

Abstract: BackgroundA cluster randomised controlled trial (RCT) of a national Kenyan mental health primary care training programme demonstrated a significant impact on the health, disability and quality of life of clients, despite a severe shortage of medicines in the clinics (Jenkins et al. Submitted 2012). As focus group methodology has been found to be a useful method of obtaining a detailed understanding of client and health worker perspectives within health systems (Sharfritz and Roberts. Health Transit Rev 4:81–85… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 20 publications
0
17
1
Order By: Relevance
“…Thus the questions were designed to elicit open ended discussion about mental health care issues rather than to specifically focus on generic health system challenges, and the information thus obtained has been reported elsewhere [12,13]. It is therefore noteworthy that the generic health system issues highlighted in this paper arose spontaneously in discussions with both the intervention group and the control group, and not in response to leading questions about specific health service problems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus the questions were designed to elicit open ended discussion about mental health care issues rather than to specifically focus on generic health system challenges, and the information thus obtained has been reported elsewhere [12,13]. It is therefore noteworthy that the generic health system issues highlighted in this paper arose spontaneously in discussions with both the intervention group and the control group, and not in response to leading questions about specific health service problems.…”
Section: Discussionmentioning
confidence: 99%
“…This paper is the third in a series reporting the results of the focus groups, the first presented the experiences and perspectives of the clients [12]; the second presented the experiences and perspectives of the health workers and their ability to understand, assess, and treat mental disorder [13]; and this third paper explores the generic health system difficulties encountered by health workers when trying to integrate mental health care into routine primary care practice.…”
Section: Introductionmentioning
confidence: 99%
“…Further limitations of the study include the fact that most of the research team for the focus group study were also involved in the randomised controlled trial. The use of both clients and health workers affords some triangulation of the findings (see accompanying papers [4,5]).…”
Section: Discussionmentioning
confidence: 99%
“…During the course of the trial Kenya, and especially Nyanza Province, experienced a severe shortage of medicines, and this was reflected in the research findings on medicine availability in the clinics participating in the trial. Nonetheless, the trial found significant improvement in the clients of the trained health workers in the intervention group compared with those in the control group [5]. Since focus group methodology has been found to be an effective way to explore health worker and client views within health system contexts [6], and at the request of the funder (the UK Department for International Development), we therefore conducted focus groups with some health workers and clients from the trial to better understand their perspectives and experiences.…”
Section: Introductionmentioning
confidence: 99%
“…Barriers to applying these tools include experts required for scoring, narrow focus on content, reliance on patient feedback, length of tools, and high costs to administer some copyrighted tools. Moreover, although common factors are important across cultures (Frank & Frank, 1991; Othieno et al, 2013), instruments developed for use by educated professionals in HICs might overly represent values and treatment philosophies that are not associated with outcomes across cultures, such as an emphasis on biomedical models (Kleinman, 1988). …”
Section: Introductionmentioning
confidence: 99%